A DESCRIPTIVE STUDY OF ENGLISH GENDER MARKERS AND THEIR USES - ARIANTI, ARIN (2007)
Gender is a term which is used to give labeling or mark of something from the nature of the object itself. Gender influences so much toward how to give treatment, view, interpret based on the characteristic had because it is looked more flexible, closer and familiar. Gender can involve everything either human or non human, animate or inanimate. It is expressed in the male and female form. This research is intended to elaborate gender words from their markers, how they are formed based on morphological process. This process can be formed directly/ indirectly which involves morpheme, affixation, allomorph, etc. This research is qualitative research. The data of this research are in the form of words which relate to gender markers. In collecting the data, the writer uses observation method which involves reading, signing, making a checklist, collecting and then classifying the data based on the type of word formation. The data sources are taken from English Grammar Books. The study reveals that there are 6 markers forms of gender words from 200 data which have been grouped in human and non human categories from the animate and inanimate terms of English and foreign languages. The gender words are formed by single form, double form, general form followed by detailed, main word preceded by two different words, main word followed by two different words, and neuter form.